2019
DOI: 10.14202/vetworld.2019.449-453
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hematological parameters of canine blood samples stored with citrate phosphate dextrose adenine-1 anticoagulated plastic vacutainers

Abstract: Aim: The effect of citrate phosphate dextrose adenine-1 on the hematological parameters of stored Nigerian indigenous dog's blood with plastic vacutainer was investigated. This was done in view of determining the viability and stability of the studied parameters for blood banking purpose. Till date, there is no literature on the stability of whole blood of Nigerian indigenous dogs for blood banking purposes. Materials and Methods: A total of six apparently adult healthy dogs were sampled, and their blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As the cells continue their metabolism, the pH is reduced at a rate proportional to the storage time [36]. A study described significantly lower pH in dogs' whole blood samples stored for more than 24 h in vacutainer plastic containing CPDA-1 [33], while another study demonstrated that goats transfused with whole blood bags stored for 15 days presented with lower pH values than animals transfused with fresh whole blood [17] . From this information, we can assume there was no intense pH reduction in the present study because the bags were stored for no more than 24 h. Measurement of venous pO 2 is useful in cases that metabolic variables such as tissue perfusion and oxygen demand are to be evaluated, as its concentration is defined by oxygen supply and consumption by tissues [11].…”
Section: Discussionmentioning
confidence: 99%
“…As the cells continue their metabolism, the pH is reduced at a rate proportional to the storage time [36]. A study described significantly lower pH in dogs' whole blood samples stored for more than 24 h in vacutainer plastic containing CPDA-1 [33], while another study demonstrated that goats transfused with whole blood bags stored for 15 days presented with lower pH values than animals transfused with fresh whole blood [17] . From this information, we can assume there was no intense pH reduction in the present study because the bags were stored for no more than 24 h. Measurement of venous pO 2 is useful in cases that metabolic variables such as tissue perfusion and oxygen demand are to be evaluated, as its concentration is defined by oxygen supply and consumption by tissues [11].…”
Section: Discussionmentioning
confidence: 99%